A polarized fast radio burst at low Galactic latitude - Petroff, E.; Burke-Spolaor, S.; Keane, E. F.; Mclaughlin, M. A.; Miller, R.; Andreoni, I.; Bailes, Matthew; Barr, E. D.; Bernard, S. R.; Bhandari, S.; Bhat, N. D. R.; Burgay, M.; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
We report on the discovery of a new fast radio burst (FRB), FRB 150215, with the Parkes radio telescope on 2015 February 15. The burst was detected in real time with a dispersion measure (DM) of 1105.6 +/- 0.8 pc cm(-3), a pulse duration of 2.8(-0.5)(+1.2) ms, and a measured peak flux density assuming that the burst was at beam centre of 0.7(-0.1)(+0.2) Jy. The FRB originated at a Galactic longitude and latitude of 24.66 degrees, 5.28 degrees and 25 degrees away from the Galactic Center. The burst was found to be 43 +/- 5 per cent linearly polarized with a rotation measure (RM) in the range -9 < RM < 12 rad m(-2) (95 per cent confidence level), consistent with zero. The burst was followed up with 11 telescopes to search for radio, optical, X-ray, gamma-ray and neutrino emission. Neither transient nor variable emission was found to be associated with the burst and no repeat pulses have been observed in 17.25 h of observing. The sightline to the burst is close to the Galactic plane and the observed physical properties of FRB 150215 demonstrate the existence of sight lines of anomalously low RM for a given electron column density. The Galactic RM foreground may approach a null value due to magnetic field reversals along the line of sight, a decreased total electron column density from the Milky Way, or some combination of these effects. A lower Galactic DM contribution might explain why this burst was detectable whereas previous searches at low latitude have had lower detection rates than those out of the plane.
Keywords: polarization; methods: data analysis; surveys; ISM: structure

Characterising the VHE diffuse emission in the central 200 parsecs of our Galaxy with H.E.S.S. - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, Michael; Balzer, A.; et al. (Astronomy & Astrophysics, 2018)
The diffuse very high-energy (VHE; > 100 GeV) gamma-ray emission observed in the central 200 pc of the Milky Way by H.E.S.S. was found to follow dense matter distribution in the central molecular zone (CMZ) up to a longitudinal distance of about 130 pc to the Galactic centre (GC), where the flux rapidly decreases. This was initially interpreted as the result of a burst-like injection of energetic particles 104 yr ago, but a recent more sensitive H.E.S.S. analysis revealed that the cosmic-ray (CR) density profile drops with the distance to the centre, making data compatible with a steady cosmic PeVatron at the GC. In this paper, we extend this analysis to obtain, for the first time, a detailed characterisation of the correlation with matter and to search for additional features and individual gamma-ray sources in the inner 200 pc. Taking advantage of 250 h of H.E.S.S. data and improved analysis techniques, we perform a detailed morphology study of the diffuse VHE emission observed from the GC ridge and reconstruct its total spectrum. To test the various contributions to the total gamma-ray emission, we used an iterative 2D maximum-likelihood approach that allows us to build a phenomenological model of the emission by summing a number of different spatial components. We show that the emission correlated with dense matter covers the full CMZ and that its flux is about half the total diffuse emission flux. We also detect some emission at higher latitude that is likely produced by hadronic collisions of CRs in less dense regions of the GC interstellar medium. We detect an additional emission component centred on the GC and extending over about 15 pc that is consistent with the existence of a strong CR density gradient and confirms the presence of a CR accelerator at the very centre of our Galaxy. We show that the spectrum of full ridge diffuse emission is compatible with that previously derived from the central regions, suggesting that a single population of particles fills the entire CMZ. Finally, we report the discovery of a VHE gamma-ray source near the GC radio arc and argue that it is produced by the pulsar wind nebula candidate G0.13-0.11.
Keywords: gamma rays: general; gamma rays: ISM; Galaxy: center; cosmic rays

Characterizing the γ-ray long-term variability of PKS 2155 - 304 with H.E.S.S. and Fermi-LAT - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; et al. (Astronomy & Astrophysics, 2017)
Studying the temporal variability of BL Lac objects at the highest energies provides unique insights into the extreme physical processes occurring in relativistic jets and in the vicinity of super-massive black holes. To this end, the long-term variability of the BL Lac object PKS 2155 304 is analyzed in the high (HE, 100MeV < E < 300 GeV) and very high energy (VHE, E > 200 GeV) gamma-ray domain. Over the course of similar to 9 yr of H. E. S. S. observations the VHE light curve in the quiescent state is consistent with a log-normal behavior. The VHE variability in this state is well described by flicker noise (power-spectral-density index beta(VHE) = 1 .10(+ 0 : 10) (0 : 13)) on timescales larger than one day. An analysis of similar to 5.5 yr of HE Fermi-LAT data gives consistent results (beta(HE) = 1 : 20(+ 0 : 21) (0 : 23), on timescales larger than 10 days) compatible with the VHE findings. The HE and VHE power spectral densities show a scale invariance across the probed time ranges. A direct linear correlation between the VHE and HE fluxes could neither be excluded nor firmly established. These long-term-variability properties are discussed and compared to the red noise behavior (beta similar to 2) seen on shorter timescales during VHE-flaring states. The difference in power spectral noise behavior at VHE energies during quiescent and flaring states provides evidence that these states are influenced by different physical processes, while the compatibility of the HE and VHE long-term results is suggestive of a common physical link as it might be introduced by an underlying jet-disk connection.
Keywords: BL Lacertae objects: individual: PKS 2155-304; Galaxies: active; Galaxies: jets; Galaxies: nuclei; Gamma rays: galaxies; Radiation mechanisms: non-thermal

Constraints on the emission region of 3C 279 during strong flares in 2014 and 2015 through VHE γ -ray observations with H.E.S.S. - Abdalla, H.; Adam, R.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; Barnard, M.; et al. (Astronomy & Astrophysics, 2019)
The flat spectrum radio quasar 3C 279 is known to exhibit pronounced variability in the high-energy (100MeV < E < 100 GeV) gamma-ray band, which is continuously monitored with Fermi-LAT. During two periods of high activity in April 2014 and June 2015 target-of-opportunity observations were undertaken with the High Energy Stereoscopic System (H.E.S.S.) in the very-high-energy (VHE, E > 100 GeV) gamma-ray domain. While the observation in 2014 provides an upper limit, the observation in 2015 results in a signal with 8 : 7 sigma significance above an energy threshold of 66 GeV. No VHE variability was detected during the 2015 observations. The VHE photon spectrum is soft and described by a power-law index of 4.2 +/- 0.3. The H.E.S.S. data along with a detailed and contemporaneous multiwavelength data set provide constraints on the physical parameters of the emission region. The minimum distance of the emission region from the central black hole was estimated using two plausible geometries of the broad-line region and three potential intrinsic spectra. The emission region is confidently placed at r greater than or similar to 1 : 7 X 1017 cm from the black hole, that is beyond the assumed distance of the broad-line region. Time-dependent leptonic and lepto-hadronic one-zone models were used to describe the evolution of the 2015 flare. Neither model can fully reproduce the observations, despite testing various parameter sets. Furthermore, the H.E.S.S. data were used to derive constraints on Lorentz invariance violation given the large redshift of 3C 279.
CRIS-Team WoS Importer:2019-07-30
Keywords: Galaxies: active; Quasars: individual: 3C 279; Radiation mechanisms: non-thermal; Relativistic processes

First ground-based measurement of sub-20 GeV to 100 GeV gamma-Rays from the Vela pulsar with HESS II - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, Michael; Barnard, M.; Becherini, Y.; Tjus, J. Becker; et al. (Astronomy & Astrophysics, 2018)
Aims. We report on the measurement and investigation of pulsed high-energy y-ray emission from the Vela pulsar, PSR B0833-45, based on observations with the largest telescope of H.E.S.S., CT5, in monoscopic mode, and on data obtained with the Fermi-LAT.
CRIS-Team WoS Importer:2020-01-15
Keywords: Gamma rays: stars; Pulsars: individual: PSR B0833-45; Radiation mechanisms: non-Thermal

First limits on the very-high energy gamma-ray afterglow emission of a fast radio burst: H.E.S.S. Observations of FRB 150418 - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; et al. (Astronomy & Astrophysics, 2017)
Aims. Following the detection of the fast radio burst FRB150418 by the SUPERB project at the Parkes radio telescope, we aim to search for very-high energy gamma-ray afterglow emission.Methods. Follow-up observations in the very-high energy gamma-ray domain were obtained with the H.E.S.S. imaging atmospheric Cherenkov telescope system within 14.5 h of the radio burst.Results. The obtained 1.4 h of gamma-ray observations are presented and discussed. At the 99% C.L. we obtained an integral upper limit on the gamma-ray flux of Phi(gamma)(E > 350 GeV) < 1.33 x 10(-8) m(-2) s(-1). Differential flux upper limits as function of the photon energy were derived and used to constrain the intrinsic high-energy afterglow emission of FRB 150418.Conclusions. No hints for high-energy afterglow emission of FRB 150418 were found. Taking absorption on the extragalactic background light into account and assuming a distance of z = 0 : 492 based on radio and optical counterpart studies and consistent with the FRB dispersion, we constrain the gamma-ray luminosity at 1 TeV to L < 5 : 1 x 10(47) erg/s at 99% C.L.
Keywords: Astroparticle physics; Gamma rays: general

Gamma-ray blazar spectra with H.E.S.S. II mono analysis: The case of PKS 2155-304 and PG 1553+113 - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; et al. (Astronomy & Astrophysics, 2017)
Context. The addition of a 28 m Cherenkov telescope (CT5) to the H.E.S.S. array extended the experiment's sensitivity to lower energies. The lowest energy threshold is obtained using monoscopic analysis of data taken with CT5, providing access to gamma-ray energies below 100 GeV for small zenith angle observations. Such an extension of the instrument's energy range is particularly beneficial for studies of active galactic nuclei with soft spectra, as expected for those at a redshift ≥0.5. The high-frequency peaked BL Lac objects PKS 2155-304 (z = 0:116) and PG 1553+113 (0:43 < z < 0:58) are among the brightest objects in the gamma-ray sky, both showing clear signatures of gamma-ray absorption at E > 100 GeV interpreted as being due to interactions with the extragalactic background light (EBL). Aims. The aims of this work are twofold: to demonstrate the monoscopic analysis of CT5 data with a low energy threshold, and to obtain accurate measurements of the spectral energy distributions (SED) of PKS 2155-304 and PG 1553+113 near their SED peaks at energies 100 GeV. Methods. Multiple observational campaigns of PKS 2155-304 and PG 1553+113 were conducted during 2013 and 2014 using the full H.E.S.S. II instrument (CT1'5). A monoscopic analysis of the data taken with the new CT5 telescope was developed along with an investigation into the systematic uncertainties on the spectral parameters which are derived from this analysis. Results. Using the data from CT5, the energy spectra of PKS 2155-304 and PG 1553+113 were reconstructed down to conservative threshold energies of 80 GeV for PKS 2155-304, which transits near zenith, and 110 GeV for the more northern PG 1553+113. The measured spectra, well fitted in both cases by a log-parabola spectral model (with a 5.0φ statistical preference for non-zero curvature for PKS 2155-304 and 4.5φ for PG 1553+113), were found consistent with spectra derived from contemporaneous Fermi-LAT data, indicating a sharp break in the observed spectra of both sources at E 100 GeV. When corrected for EBL absorption, the intrinsic H.E.S.S. II mono and Fermi-LAT spectrum of PKS 2155-304 was found to show significant curvature. For PG 1553+113, however, no significant detection of curvature in the intrinsic spectrum could be found within statistical and systematic uncertainties.
Keywords: BL Lacertae objects: individual: PG 1553+113; BL Lacertae objects: individual: PKS 2155-304; Galaxies: active; Gamma rays: galaxies

HESS and Suzaku observations of the Vela X pulsar wind nebula - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Backes, M.; Barnard, M.; Becherini, Y.; Berge, D.; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2019)
Context. Pulsar wind nebulae (PWNe) represent the most prominent population of Galactic very-high-energy gamma-ray sources and are thought to be an efficient source of leptonic cosmic rays. Vela X is a nearby middle-aged PWN, which shows bright X-ray and TeV gamma-ray emission towards an elongated structure called the cocoon.
CRIS-Team WoS Importer:2019-07-23
Keywords: Gamma rays: stars; Pulsars: individual: PSR B0833-45; Radiation mechanisms: non-thermal; Stars: winds; outflows; Acceleration of particles

HESS J1741-302: a hidden accelerator in the Galactic plane - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Angüner, E. O.; Arakawa, M.; Armand, C.; Arrieta, M.; Backes, M.; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Astronomy & Astrophysics, 2018)
The H.E.S.S. Collaboration has discovered a new very high energy (VHE, E > 0.1 TeV) gamma-ray source, HESS J1741-302, located in the Galactic plane. Despite several attempts to constrain its nature, no plausible counterpart has been found so far at X-ray and MeV/GeV gamma-ray energies, and the source remains unidentified. An analysis of 145-h of observations of HESS J1741-302 at VHEs has revealed a steady and relatively weak TeV source (similar to 1% of the Crab Nebula flux), with a spectral index of Gamma = 2.3 +/- 0.2(stat) +/- 0.2(sys), extending to energies up to 10 TeV without any clear signature of a cut-off. In a hadronic scenario, such a spectrum implies an object with particle acceleration up to energies of several hundred TeV. Contrary to most H.E.S.S. unidentified sources, the angular size of HESS J1741-302 is compatible with the H.E.S.S. point spread function at VHEs, with an extension constrained to be below 0.068 degrees at a 99% confidence level. The gamma-ray emission detected by H.E.S.S. can be explained both within a hadronic scenario, due to collisions of protons with energies of hundreds of TeV with dense molecular clouds, and in a leptonic scenario, as a relic pulsar wind nebula, possibly powered by the middle-aged (20 kyr) pulsar PSR B1737-30. A binary scenario, related to the compact radio source 1LC 358.266+0.038 found to be spatially coincident with the best fit position of HESS J1741-302, is also envisaged.
Keywords: gamma rays: ISM; gamma rays: general; cosmic rays; ISM: clouds

H.E.S.S. Limits on Linelike Dark Matter Signatures in the 100 GeV to 2 TeV Energy Range Close to the Galactic Center - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; et al. (Physical Review Letters, 2016)
A search for dark matter linelike signals iss performed in the vicinity of the Galactic Center by the H.E.S.S. experiment on observational data taken in 2014. An unbinned likelihood analysis iss developed to improve the sensitivity to linelike signals. The upgraded analysis along with newer data extend the energy coverage of the previous measurement down to 100 GeV. The 18 h of data collected with the H.E.S.S. array allow one to rule out at 95% C.L. the presence of a 130 GeV line (at l=-1.5°, b=0° and for a dark matter profile centered at this location) previously reported in Fermi-LAT data. This new analysis overlaps significantly in energy with previous Fermi-LAT and H.E.S.S. results. No significant excess associated with dark matter annihilations was found in the energy range of 100 GeV to 2 TeV and upper limits on the gamma-ray flux and the velocity weighted annihilation cross section are derived adopting an Einasto dark matter halo profile. Expected limits for present and future large statistics H.E.S.S. observations are also given.

HESS observations of the flaring gravitationally lensed galaxy PKS 1830-211 - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, M.; Barnard, M.; Becherini, Y.; Tjus, J. Becker; et al. (Monthly Notices of the Royal Astronomical Society, 2019)
PKS 1830-211 is a known macrolensed quasar located at a redshift of z = 2.5. Its highenergy gamma-ray emission has been detected with the Fermi-Large Area Telescope (LAT) instrument and evidence for lensing was obtained by several authors from its high-energy data. Observations of PKS 1830-211 were taken with the High Energy Stereoscopic System (H.E.S.S.) array of Imaging Atmospheric Cherenkov Telescopes in 2014 August, following a flare alert by the Fermi-LAT Collaboration. The H.E.S.S observations were aimed at detecting a gamma-ray flare delayed by 20-27 d from the alert flare, as expected from observations at other wavelengths. More than 12 h of good-quality data were taken with an analysis threshold of similar to 67 GeV. The significance of a potential signal is computed as a function of the date and the average significance over the whole period. Data are compared to simultaneous observations by Fermi-LAT. No photon excess or significant signal is detected. An upper limit on PKS 1830-211 flux above 67 GeV is computed and compared to the extrapolation of the Fermi-LAT flare spectrum.
CRIS-Team WoS Importer:2019-07-26
Keywords: gamma-rays: galaxies; gravitational lensing: strong; diffuse radiation

Measurement of the EBL spectral energy distribution using the VHE gamma-ray spectra of HESS blazars - Abdalla, H.; Abramowski, A.; Aharonian, F.; Ait Benkhali, F.; Akhperjanian, A. G.; Andersson, T.; Angüner, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; et al. (Astronomy & Astrophysics, 2017)
Very high-energy gamma rays (VHE, E greater than or similar to 100 GeV) propagating over cosmological distances can interact with the low-energy photons of the extragalactic background light (EBL) and produce electron-positron pairs. The transparency of the Universe to VHE gamma rays is then directly related to the spectral energy distribution (SED) of the EBL. The observation of features in the VHE energy spectra of extragalactic sources allows the EBL to be measured, which otherwise is very difficult. An EBL model-independent measurement of the EBL SED with the H.E.S.S. array of Cherenkov telescopes is presented. It was obtained by extracting the EBL absorption signal from the reanalysis of high-quality spectra of blazars. From H.E.S.S. data alone the EBL signature is detected at a significance of 9.5 sigma, and the intensity of the EBL obtained in different spectral bands is presented together with the associated gamma-ray horizon.
CRIS-Team WoS Importer:2020-01-15
Keywords: Infrared: diffuse background; Cosmic background radiation; Gamma rays: galaxies; BL Lacertae objects: general

Multi-messenger Observations of a Binary Neutron Star Merger - Abbott, B. P.; Abbott, R.; Abbott, T. D.; Acernese, F.; Ackley, K.; Adams, C.; Adams, T.; Addesso, Paolo; Adhikari, R. X.; Adya, V. B.; Affeldt, C.; Afrough, M.; et al. (Astrophysical Journal Letters, 2017)
On 2017 August 17 a binary neutron star coalescence candidate (later designated GW170817) with merger time 12:41:04 UTC was observed through gravitational waves by the Advanced LIGO and Advanced Virgo detectors. The Fermi Gamma-ray Burst Monitor independently detected a gamma-ray burst (GRB 170817A) with a time delay of similar to 1.7 s with respect to the merger time. From the gravitational-wave signal, the source was initially localized to a sky region of 31 deg(2) at a luminosity distance of 40(-8)(+8) Mpc and with component masses consistent with neutron stars. The component masses were later measured to be in the range 0.86 to 2.26 M-circle dot. An extensive observing campaign was launched across the electromagnetic spectrum leading to the discovery of a bright optical transient (SSS17a, now with the IAU identification of AT 2017gfo) in NGC 4993 (at similar to 40 Mpc) less than 11 hours after the merger by the One-Meter, Two Hemisphere (1M2H) team using the 1 m Swope Telescope. The optical transient was independently detected by multiple teams within an hour. Subsequent observations targeted the object and its environment. Early ultraviolet observations revealed a blue transient that faded within 48 hours. Optical and infrared observations showed a redward evolution over similar to 10 days. Following early non-detections, X-ray and radio emission were discovered at the transient's position similar to 9 and similar to 16 days, respectively, after the merger. Both the X-ray and radio emission likely arise from a physical process that is distinct from the one that generates the UV/optical/near-infrared emission. No ultra-high-energy gamma-rays and no neutrino candidates consistent with the source were found in follow-up searches. These observations support the hypothesis that GW170817 was produced by the merger of two neutron stars in NGC4993 followed by a short gamma-ray burst (GRB 170817A) and a kilonova/macronova powered by the radioactive decay of r-process nuclei synthesized in the ejecta.
Keywords: gravitational waves; stars: neutron

Particle transport within the pulsar wind nebula HESS J1825-137 - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, M.; Barnard, Monica; Becherini, Y.; Tjus, J. Becker; et al. (Astronomy & Astrophysics, 2019)
Context. We present a detailed view of the pulsar wind nebula (PWN) HESS J1825-137. We aim to constrain the mechanisms dominating the particle transport within the nebula, accounting for its anomalously large size and spectral characteristics. Aims. The nebula was studied using a deep exposure from over 12 years of H.E.S.S. I operation, together with data from H.E.S.S. II that improve the low-energy sensitivity. Enhanced energy-dependent morphological and spatially resolved spectral analyses probe the very high energy (VHE, E > 0.1 TeV) γ-ray properties of the nebula. Methods. The nebula emission is revealed to extend out to 1.5° from the pulsar, ∼1.5 times farther than previously seen, making HESS J1825-137, with an intrinsic diameter of ∼100 pc, potentially the largest γ-ray PWN currently known. Characterising the strongly energy-dependent morphology of the nebula enables us to constrain the particle transport mechanisms. A dependence of the nebula extent with energy of RE α with α = -0.29 ± 0.04 stat ± 0.05 sys disfavours a pure diffusion scenario for particle transport within the nebula. The total γ-ray flux of the nebula above 1 TeV is found to be (1.12 ± 0.03 stat ± 0.25 sys ) × 10 -11 cm -2 s -1 , corresponding to ∼64% of the flux of the Crab nebula. Results. HESS J1825-137 is a PWN with clearly energy-dependent morphology at VHE γ-ray energies. This source is used as a laboratory to investigate particle transport within intermediate-age PWNe. Based on deep observations of this highly spatially extended PWN, we produce a spectral map of the region that provides insights into the spectral variation within the nebula.
CRIS-Team Scopus Importer:2019-05-02
Keywords: gamma rays: general; acceleration of particles; convection; diffusion; pulsars: general

Population study of Galactic supernova remnants at very high gamma-ray energies with HESS - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Anguener, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Astronomy & Astrophysics, 2018)
Shell-type supernova remnants (SNRs) are considered prime candidates for the acceleration of Galactic cosmic rays (CRs) up to the knee of the CR spectrum at E approximate to 3 x 10(15) eV. Our MilkyWay galaxy hosts more than 350 SNRs discovered at radio wavelengths and at high energies, of which 220 fall into the H.E.S.S. Galactic Plane Survey (HGPS) region. Of those, only 50 SNRs are coincident with a H.E.S.S source and in 8 cases the very high-energy (VHE) emission is firmly identified as an SNR. The H.E.S.S. GPS provides us with a legacy for SNR population study in VHE gamma-rays and we use this rich data set to extract VHE flux upper limits from all undetected SNRs. Overall, the derived flux upper limits are not in contradiction with the canonical CR paradigm. Assuming this paradigm holds true, we can constrain typical ambient density values around shell-type SNRs to n <= 7 cm(-3) and electron-to-proton energy fractions above 10 TeV to epsilon(ep) <= 5 x 10(-3). Furthermore, comparisons of VHE with radio luminosities in non-interacting SNRs reveal a behaviour that is in agreement with the theory of magnetic field amplification at shell-type SNRs.
Keywords: gamma rays: general; ISM: supernova remnants

Prospects for Cherenkov Telescope Array Observations of the Young Supernova Remnant RX J1713.73946 - Acero, F.; Aloisio, R.; Amans, J.; Amato, E.; Antonelli, L. A.; Aramo, C.; Armstrong, T.; Arqueros, F.; Asano, K.; Ashley, M.; Backes, M.; Balazs, C.; et al. (Astrophysical Journal, 2017)
Keywords: cosmic rays; gamma rays: ISM; ISM: individual objects: RX J1713.7 dash3946; G347.3 dash0.5

Resolving the Crab pulsar wind nebula at teraelectronvolt energies - Abdalla, H.; Aharonian, F.; Ait Benkhali, F.; Angüner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Backes, M.; Barnard, M.; Becherini, Y.; Becker Tjus, J.; Berge, D.; et al. (Nature Astronomy, 2019)
The Crab nebula is one of the most-studied cosmic particle accelerators, shining brightly across the entire electromagnetic spectrum up to very-high-energy gamma rays1,2. It is known from observations in the radio to gamma-ray part of the spectrum that the nebula is powered by a pulsar, which converts most of its rotational energy losses into a highly relativistic outflow. This outflow powers a pulsar wind nebula, a region of up to ten light-years across, filled with relativistic electrons and positrons. These particles emit synchrotron photons in the ambient magnetic field and produce very-high-energy gamma rays by Compton up-scattering of ambient low-energy photons. Although the synchrotron morphology of the nebula is well established, it has not been known from which region the very-high-energy gamma rays are emitted3–8. Here we report that the Crab nebula has an angular extension at gamma-ray energies of 52 arcseconds (assuming a Gaussian source width), much larger than at X-ray energies. This result closes a gap in the multi-wavelength coverage of the nebula, revealing the emission region of the highest-energy gamma rays. These gamma rays enable us to probe a previously inaccessible electron and positron energy range. We find that simulations of the electromagnetic emission reproduce our measurement, providing a non-trivial test of our understanding of particle acceleration in the Crab nebula.
CRIS-Team Scopus Importer:2019-11-15

Search for Dark Matter Annihilations towards the Inner Galactic Halo from 10 Years of Observations with HESS - Abdallah, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Physical Review Letters, 2016)
The inner region of the Milky Way halo harbors a large amount of dark matter (DM). Given its proximity, it is one of the most promising targets to look for DM. We report on a search for the annihilations of DM particles using gamma-ray observations towards the inner 300 pc of the Milky Way, with the H.E.S.S. array of ground-based Cherenkov telescopes. The analysis is based on a 2D maximum likelihood method using Galactic Center (GC) data accumulated by H.E.S.S. over the last 10 years (2004-2014), and does not show any significant gamma-ray signal above background. Assuming Einasto and Navarro-Frenk-White DM density profiles at the GC, we derive upper limits on the annihilation cross section <sigma nu="">. These constraints are the strongest obtained so far in the TeV DM mass range and improve upon previous limits by a factor 5. For the Einasto profile, the constraints reach <sigma nu=""> values of 6 x 10(-26) cm(3) s(-1) in the W+W- channel for a DM particle mass of 1.5 TeV, and 2 x 10(-26) cm(3) s(-1) in the tau(+)tau(-) channel for a 1 TeV mass. For the first time, ground-based gamma-ray observations have reached sufficient sensitivity to probe <sigma nu=""> values expected from the thermal relic density for TeV DM particles.</sigma></sigma></sigma>

Search for gamma-Ray Line Signals from Dark Matter Annihilations in the Inner Galactic Halo from 10 Years of Observations with HESS - Abdallah, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Physical Review Letters, 2018)
Spectral lines are among the most powerful signatures for dark matter (DM) annihilation searches in very-high-energy gamma rays. The central region of the Milky Way halo is one of the most promising targets given its large amount of DM and proximity to Earth. We report on a search for a monoenergetic spectral line from self-annihilations of DM particles in the energy range from 300 GeV to 70 TeV using a two-dimensional maximum likelihood method taking advantage of both the spectral and spatial features of the signal versus background. The analysis makes use of Galactic center observations accumulated over ten years (2004-2014) with the H.E.S.S. array of ground-based Cherenkov telescopes. No significant gamma-ray excess above the background is found. We derive upper limits on the annihilation cross section (sigma v) for monoenergetic DM lines at the level of 4 x 10(-28) cm(3) s(-1) at 1 TeV, assuming an Einasto DM profile for the Milky Way halo. For a DM mass of 1 TeV, they improve over the previous ones by a factor of 6. The present constraints are the strongest obtained so far for DM particles in the mass range 300 GeV-70 TeV. Ground-based gamma-ray observations have reached sufficient sensitivity to explore relevant velocity-averaged cross sections for DM annihilation into two gamma-ray photons at the level expected from the thermal relic density for TeV DM particles.

Simulation of diffusive particle propagation and related TeV γ-ray emission at the Galactic Center - van Eldik, Christopher; Ziegler, Alexander (34th International Cosmic Ray Conference (ICRC2015), 2015)

Studies towards an understanding of global array pointing for the cherenkov telescope array - Eschbach, Stefan; Ziegler, Alexander; van Eldik, Christopher; Veh, Johannes; Berge, David; Gaug, Markus (34th International Cosmic Ray Conference (ICRC2015), 2015)
Current arrays of Imaging Atmospheric Cherenkov Telescopes (IACTs) routinely achieve an astrometric point-source location accuracy of 20-30 seconds of arc (given large photon statistics), which is well below the angular resolution obtained for individual photons. The location accuracy is mainly limited by systematic uncertainties due to possible deformations of the telescopes' structures, causing a mis-orientation between the nominal optical axes of the telescopes and their actual pointing directions. Usually, only a subset of telescopes is triggered for a given gammaray event, and their mis-orientations enter the gamma-ray direction reconstruction in a combined manner. Hence, in general, the average location accuracy for a set of gamma-ray observations depends in a complex way on the individual telescope accuracy and the geometry of the array, but also on the observing conditions, the energy spectrum of the source and the chosen event selection cuts. For the proposed Cherenkov Telescope Array (CTA), a post-calibration point-source location accuracy of 3 seconds of arc is aimed for under favorable observing conditions and for gamma-ray energies exceeding 100 GeV. In this contribution, results of first studies on the location accuracy are presented. These studies are based on a toy Monte Carlo simulation of a typical CTA-South array layout, taking into account the expected trigger rates of the different CTA telescope types and the gamma-ray spectrum of the simulated source. With this simulation code it is possible to study the location accuracy as a function of arbitrary telescope mis-orientations and for typical observing patterns on the sky. Results are presented for various scenarios, including one for which all individual telescopes are randomly mis-oriented within their specified limits. The study provides solid lower limits for the expected source location accuracy of CTA, and can be easily extended to include various other important effects like atmospheric refraction or partial cloud coverage.

The 2014 TeV γ-Ray Flare of Mrk 501 Seen with H.E.S.S.: Temporal and Spectral Constraints on Lorentz Invariance Violation - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, M.; Barnard, M.; Becherini, Y.; Tjus, J. Becker; et al. (Astrophysical Journal, 2019)
The blazar Mrk 501 (z = 0.034) was observed at very-high-energy (VHE, E ≳ 100 GeV) gamma-ray wavelengths during a bright flare on the night of 2014 June 23-24 (MJD 56832) with the H.E.S.S. phase-II array of Cherenkov telescopes. Data taken that night by H.E.S.S. at large zenith angle reveal an exceptional number of gamma-ray photons at multi-TeV energies, with rapid flux variability and an energy coverage extending significantly up to 20 TeV. This data set is used to constrain Lorentz invariance violation (LIV) using two independent channels: a temporal approach considers the possibility of an energy dependence in the arrival time of gamma-rays, whereas a spectral approach considers the possibility of modifications to the interaction of VHE gamma-rays with extragalactic background light (EBL) photons. The non-detection of energy-dependent time delays and the non-observation of deviations between the measured spectrum and that of a supposed power-law intrinsic spectrum with standard EBL attenuation are used independently to derive strong constraints on the energy scale of LIV (E QG ) in the subluminal scenario for linear and quadratic perturbations in the dispersion relation of photons. For the case of linear perturbations, the 95% confidence level limits obtained are E QG,1 > 3.6 ×10 17 GeV using the temporal approach and E QG,1 > 2.6 ×10 19 GeV using the spectral approach. For the case of quadratic perturbations, the limits obtained are E QG,2 > 8.5 ×10 10 GeV using the temporal approach and E QG,2 > 7.8 ×10 11 GeV using the spectral approach.
CRIS-Team Scopus Importer:2019-05-14
Keywords: astroparticle physics; BL Lacertae objects: individual (Mrk 501); gamma rays: galaxies

The gamma-ray spectrum of the core of Centaurus A as observed with HESS and Fermi-LAT - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Armand, C.; Arrieta, M.; Backes, Michael; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Astronomy & Astrophysics, 2018)
Centaurus A (Cen A) is the nearest radio galaxy discovered as a very-high-energy (VHE; 100 GeV-100 TeV) gamma-ray source by the High Energy Stereoscopic System (H.E.S.S.). It is a faint VHE gamma-ray emitter, though its VHE flux exceeds both the extrapolation from early Fermi-LAT observations as well as expectations from a (misaligned) single-zone synchrotron-self Compton (SSC) description. The latter satisfactorily reproduces the emission from Cen A at lower energies up to a few GeV. New observations with H.E.S.S., comparable in exposure time to those previously reported, were performed and eight years of Fermi-LAT data were accumulated to clarify the spectral characteristics of the gamma-ray emission from the core of Cen A. The results allow us for the first time to achieve the goal of constructing a representative, contemporaneous gamma-ray core spectrum of Cen A over almost five orders of magnitude in energy. Advanced analysis methods, including the template fitting method, allow detection in the VHE range of the core with a statistical significance of 12 sigma on the basis of 213 hours of total exposure time. The spectrum in the energy range of 250 GeV-6 TeV is compatible with a power-law function with a photon index Gamma = 2.52 +/- 0.13(stat) +/- 0.20(sys). An updated Fermi-LAT analysis provides evidence for spectral hardening by Delta Gamma similar or equal to 0.4 +/- 0.1 at gamma-ray energies above 2.8(-0.6)(+1.0) GeV at a level of 4.0 sigma. The fact that the spectrum hardens at GeV energies and extends into the VHE regime disfavour a single-zone SSC interpretation for the overall spectral energy distribution (SED) of the core and is suggestive of a new gamma-ray emitting component connecting the high-energy emission above the break energy to the one observed at VHE energies. The absence of significant variability at both GeV and TeV energies does not yet allow disentanglement of the physical nature of this component, though a jet-related origin is possible and a simple two-zone SED model fit is provided to this end.
CRIS-Team WoS Importer:2020-01-15
Keywords: Radiation mechanisms: non-thermal; Gamma rays: galaxies

The HESS Galactic plane survey - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Anguener, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, Michael; Balzer, A.; Barnard, Monica; Becherini, Y.; et al. (Astronomy & Astrophysics, 2018)
We present the results of the most comprehensive survey of the Galactic plane in very high-energy (VHE) gamma-rays, including a public release of Galactic sky maps, a catalog of VHE sources, and the discovery of 16 new sources of VHE gamma-rays. The High Energy Spectroscopic System (H.E.S.S.) Galactic plane survey (HGPS) was a decade-long observation program carried out by the H.E.S.S. I array of Cherenkov telescopes in Namibia from 2004 to 2013. The observations amount to nearly 2700 h of quality-selected data, covering the Galactic plane at longitudes from l = 250 degrees to 65 degrees and latitudes vertical bar b vertical bar <= 3 degrees. In addition to the unprecedented spatial coverage, the HGPS also features a relatively high angular resolution (0.08 degrees approximate to 5 arcmin mean point spread function 68% containment radius), sensitivity (less than or similar to 1.5% Crab flux for point-like sources), and energy range (0.2-100 TeV). We constructed a catalog of VHE gamma-ray sources from the HGPS data set with a systematic procedure for both source detection and characterization of morphology and spectrum. We present this likelihood-based method in detail, including the introduction of a model component to account for unresolved, large-scale emission along the Galactic plane. In total, the resulting HGPS catalog contains 78 VHE sources, of which 14 are not reanalyzed here, for example, due to their complex morphology, namely shell-like sources and the Galactic center region. Where possible, we provide a firm identification of the VHE source or plausible associations with sources in other astronomical catalogs. We also studied the characteristics of the VHE sources with source parameter distributions. 16 new sources were previously unknown or unpublished, and we individually discuss their identifications or possible associations. We firmly identified 31 sources as pulsar wind nebulae (PWNe), supernova remnants (SNRs), composite SNRs, or gamma-ray binaries. Among the 47 sources not yet identified, most of them (36) have possible associations with cataloged objects, notably PWNe and energetic pulsars that could power VHE PWNe.
Keywords: gamma rays: general; surveys; Galaxy: general

The starburst galaxy NGC 253 revisited by H.E.S.S. and Fermi-LAT - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, Michael; Barnard, Monica; Becherini, Y.; Tjus, J. Becker; et al. (Astronomy & Astrophysics, 2018)
Context. NGC 253 is one of only two starburst galaxies found to emit gamma-rays from hundreds of MeV to multi-TeV energies. Accurate measurements of the very-high-energy (VHE; E> 100 GeV) and high-energy (HE; E > 60 MeV) spectra are crucial to study the underlying particle accelerators, probe the dominant emission mechanism(s) and to study cosmic-ray interaction and transport.
CRIS-Team WoS Importer:2020-01-15
Keywords: Astroparticle physics; Galaxies: starburst; Gamma rays: galaxies

The supernova remnant W49B as seen with HESS and Fermi-LAT - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, O.; Arrieta, M.; Aubert, P.; Backes, Michael; Balzer, A.; Barnard, Monica; et al. (Astronomy & Astrophysics, 2018)
The supernova remnant (SNR) W49B originated from a core-collapse supernova that occurred between one and four thousand years ago, and subsequently evolved into a mixed-morphology remnant, which is interacting with molecular clouds (MC). Gamma-ray observations of SNR-MC associations are a powerful tool to constrain the origin of Galactic cosmic rays, as they can probe the acceleration of hadrons through their interaction with the surrounding medium and subsequent emission of non-thermal photons. We report the detection of a gamma-ray source coincident with W49B at very high energies (VHE; E > 100 GeV) with the H.E.S.S. Cherenkov telescopes together with a study of the source with five years of Fermi-LAT high-energy gamma-ray (0.06-300 GeV) data. The smoothly connected, combined source spectrum, measured from 60 MeV to multi-TeV energies, shows two significant spectral breaks at 304 +/- 20 MeV and 8.4(-2.5)(+2.5) GeV; the latter is constrained by the joint fit from the two instruments. The detected spectral features are similar to those observed in several other SNR-MC associations and are found to be indicative of gamma-ray emission produced through neutral-pion decay.
Keywords: gamma rays: general; ISM: supernova remnants; ISM: clouds

Upper limits on very-high-energy gamma-ray emission from core-collapse supernovae observed with HESS - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguener, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Ashkar, H.; Backes, Michael; Martins, V. Barbosa; Barnard, M.; Becherini, Y.; et al. (Astronomy & Astrophysics, 2019)
Young core-collapse supernovae with dense-wind progenitors may be able to accelerate cosmic-ray hadrons beyond the knee of the cosmic-ray spectrum, and this may result in measurable gamma-ray emission. We searched for gamma-ray emission from ten super- novae observed with the High Energy Stereoscopic System (H.E.S.S.) within a year of the supernova event. Nine supernovae were observed serendipitously in the H.E.S.S. data collected between December 2003 and December 2014, with exposure times ranging from 1.4 to 53 h. In addition we observed SN 2016adj as a target of opportunity in February 2016 for 13 h. No significant gamma-ray emission has been detected for any of the objects, and upper limits on the >1 TeV gamma-ray flux of the order of similar to 10(-13) cm(-)(2)s(-1) are established, corresponding to upper limits on the luminosities in the range similar to 2 x 10(39) to similar to 1 x 10(42) erg s(-1). These values are used to place model-dependent constraints on the mass-loss rates of the progenitor stars, implying upper limits between similar to 2 x 10(-5) and similar to 2 x 10(-3) M-circle dot yr(-1) under reasonable assumptions on the particle acceleration parameters.
CRIS-Team WoS Importer:2019-06-28

VHE gamma-ray discovery and multiwavelength study of the blazar 1ES 2322-409 - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, M.; Barnard, M.; Becherini, Y.; Tjus, J. Becker; et al. (Monthly Notices of the Royal Astronomical Society, 2019)
A hotspot at a position compatible with the BL. Lac object 1ES 2322-409 was serendipitously detected with H.E.S.S. during observations performed in 2004 and 2006 on the blazar PKS 2316-423. Additional data on 1ES 2322-409 were taken in 2011 and 2012, leading to a total live-time of 22.3 h. Point-like very-high-energy (VHE; E > 100 GeV) gamma-ray emission is detected from a source centred on the IFS 2322-409 position, with an excess of 116.7 events at a significance of 6.0 sigma. The average VHE gamma-ray spectrum is well described with a power law with a photon index Gamma = 3.40 +/- 0.66(stat) +/- 0.20(sys) and an integral flux Phi(E > 200 GeV) = (3.11 +/- 0.71(stat) 0.62(sys)) x 10(-2)cm(-2)s(-1), which corresponds to 1.1 per cent of the Crab nebula flux above 200 GeV. Multiwavelength data obtained with Fermi LAT, Swift XRT and UVOT, RXTE PCA, ATOM, and additional data from WISE, GROND, and Catalina are also used to characterize the broad-band non-thermal emission of lES 2322-409. The multiwavelength behaviour indicates day-scale variability. Swift UVOT and XRT data show strong variability at longer scales. A spectral energy distribution (SED) is built from contemporaneous observations obtained around a high state identified in Swift data. A modelling of the SED is performed with a stationary homogeneous one-zone synchrotronself-Compton leptonic model. The redshift of the source being unknown, two plausible values were tested for the modelling. A systematic scan of the model parameters space is performed, resulting in a well-constrained combination of values providing a good description of the broad-band behaviour of 1ES 2322-409.
CRIS-Team WoS Importer:2019-04-09
Keywords: BL Lacertae objects: individual: 1ES 2322-409; galaxies: active; gamma-rays: galaxies; Radiation mechanisms: non-thermal